Reconciliation between Immunity Assessed for the Diplomatic Bag and Considered National Security - Hasan, Ali; Jafaar, Mahmood (Journal of Legal Sciences, 2023)
The diplomatic bag is one of the important means of communication used by the diplomatic mission to communicate with the government of the sending country and its consulates, as well as the missions in other countries. The diplomatic bag was granted absolute immunity against opening, seizing and inspection in order to effectively perform the function entrusted to it. The practical reality revealed the exploitation of the diplomatic bag to smuggle drugs and shipments of weapons and explosives that harmed the national security of the receiving country. The International Law Committee avoided the matter and reconciled the interest of the immunity of the diplomatic bag with the interest of the state in preserving national security and sovereignty.